SAMPRAPTI: A COMPREHENSIVE REVIEW OF ITS CLINICAL SIGNIFICANCE AND APPLICATIONS (International Journal of Food and Nutritional Sciences, 2022)
In Ayurveda, Nidana Panchaka serves as a crucial tool for diagnosing diseases. Ayurvedic diagnostic methods are broadly divided into Rogi Pariksha (patient examination) and Roga Pariksha (disease examination). Roga Pariksha offers comprehensive insights into the illness and is performed prior to initiating treatment. The five diagnostic methods in Ayurveda, collectively known as Nidana Panchaka, include Nidana, Purvarupa, Rupa, Upashaya, and Samprapti, all of which fall under Roga Pariksha. Among these, Samprapti is a key element, essential for determining the treatment approach. In a clinical setting, taking a thorough patient history is of paramount importance, as it leads the clinician to an accurate diagnosis. Proper diagnosis forms the foundation for effective treatment, while misdiagnosis or lack of recognition of the disease can result in improper care. Therefore, diagnosis must always precede treatment. Samprapti not only aids in disease diagnosis but also provides valuable information on the prognosis, management, and differential diagnosis of the condition.